Effect of microwave treatment on current flow mechanism in ohmic contacts to GaN - Sheremet, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The temperature dependence of contact resistivity ρс of Ti-Al-TiB₂-Au ohmic contacts to n-GaN and effect of microwave treatment on ρс are investigated. The obtained dependences are described using a model of current flow via metal shunts associated with dislocations, the current being limited by diffusion supply of electrons. It is shown that microwave treatment increases the dislocation density in the near-contact region of contact structure and reduces the relative spread of resistivity values of contacts formed on the wafer.